2015
DOI: 10.2174/1389200216666150206130058
|View full text |Cite
|
Sign up to set email alerts
|

CYP1B1: A Unique Gene with Unique Characteristics

Abstract: CYP1B1, a recently described dioxin inducible oxidoreductase, is a member of the cytochrome P450 superfamily involved in the metabolism of estradiol, retinol, benzo[a]pyrene, tamoxifen, melatonin, sterols etc. It plays important roles in numerous physiological processes and is expressed at mRNA level in many tissues and anatomical compartments. CYP1B1 has been implicated in scores of disorders. Analyses of the recent studies suggest that CYP1B1 can serve as a universal/ideal cancer marker and a candidate gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…They metabolize tobacco constituents—benzo(a)pyrene and nicotine, respectively—and are responsible for smoking-mediated carcinogenesis as well as liver toxicity [31,32]. In addition to cancers, CYP1B1 is known to be induced under many disease conditions and has been implicated as an important biological marker for the predictive diagnosis of developmental disorders [33]. Plasma exosomes containing CYP2A6 may be used as biological markers for nicotine dependence, because it is known to be induced by nicotine and rapidly metabolizes nicotine in the liver [33].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They metabolize tobacco constituents—benzo(a)pyrene and nicotine, respectively—and are responsible for smoking-mediated carcinogenesis as well as liver toxicity [31,32]. In addition to cancers, CYP1B1 is known to be induced under many disease conditions and has been implicated as an important biological marker for the predictive diagnosis of developmental disorders [33]. Plasma exosomes containing CYP2A6 may be used as biological markers for nicotine dependence, because it is known to be induced by nicotine and rapidly metabolizes nicotine in the liver [33].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to cancers, CYP1B1 is known to be induced under many disease conditions and has been implicated as an important biological marker for the predictive diagnosis of developmental disorders [33]. Plasma exosomes containing CYP2A6 may be used as biological markers for nicotine dependence, because it is known to be induced by nicotine and rapidly metabolizes nicotine in the liver [33]. Among the important drug-metabolic CYP enzymes, CYP3A4 showed detectable levels of both mRNA and proteins, as well as H 2 O 2 -dependent enzyme activity.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, the most well studied splice variants of CYP1B1 all represent severe truncations or deletion mutants, not exon skipping (Tanwar et al, 2009), and CYP1B1 retains an unusual, elongated C-terminus, further distinguishing it from other human P450 forms. The CYP1B1 gene is also uniquely located on chromosome 2 at locus 2p21-22, which in humans is derived from an ancient fusion of chimpanzee chromosomes 2a and 2b (Faiq et al, 2014). It is difficult to speculate why the CYP1B1 gene is organized so differently from closely related CYP1A genes located on chromosome 15.…”
Section: Meta-analysis Of Alternative Gene Splicing In the Cytochromementioning
confidence: 99%
“…Our study demonstrated for the first time that Cyp2c38 is downregulated by PCN or TCPOBOP treatment and suggests that miR-26b-3p may play a role in Cyp2c38's regulation. In addition, our results showed that the mRNA expression of Cyp1b1, which is known to metabolize several pro-carcinogens, 20) was increased in response to PCN. This result is consistent with recent reports from two separate groups indicating that PXR activation up-regulates Cyp1b1's expression in vascular endothelial cells 21) or skin 22) ; however, the induction mechanism was unclear.…”
Section: )mentioning
confidence: 57%